Properties, Powers and Structures : Issues in the Metaphysics of Realism. - Bird, Alexander (Routledge studies in metaphysics., 2011)
While the phrase ""metaphysics of science"" has been used from time to time, it has only recently begun to denote a specific research area where metaphysics meets philosophy of science--and the sciences themselves. The essays in this volume demonstrate that metaphysics of science is an innovative field of research in its own right. The principle areas covered are: The modal metaphysics of properties: What is the essential nature of natural properties? Are all properties essentially categorical? Are they all essentially dispositions, or are some categorical and others dispositional? Realism in.